PERANCANGAN PROYEK DEPARTMENT STORE DENGAN PENDALAMAN BEHAVIORAL ARCHITECTURE OLEH KONSULTAN ARSITEKTUR INTERIOR AERI ATELIER - Clarissa Averina; Melania Rahadiyanti (KREASI, 2023)
The final assignment is entitled “Project Design Department Store with Deep Behavioral Architecture by InteriorArchitecture Consultant Aeri Atelier” which contains business plans specializing in behavioral architecture indesigning a building. It is due to issues related to the COVID-19 pandemic spreading; many customers are nowtransferring from online to offline department store shopping to online e-commerce from home. Department storesare becoming less common and vulnerable, detrimental to economic development. The author hopes the designproject department store can not only provide facilities for shopping directly but also as a means of leisure which caninfluence well-being and consumer behavior visitors and able to increase customer buying behavior. The methodsused in this design are observation, interviews and data collection, literature study, typology study, and designthinking, which is the process of designing a solution to existing problems. Aeri Atelier will apply the deepeningbehavioral architecture in a room that is designed and provides benefits to the room users. With value offered,the owner of Rosa Fashion Department Store agreed to create a supportive environment positive building users,and an ambiance that experiences visitors while shopping. Approach behavioral architecture is applied throughspatial planning, the atmosphere of the room and building, and the materials used.